Nurturing Policyholder Satisfaction through Customer-Centric Strategies - Karki, Dipendra; Dahal, Rewan Kumar; Shrestha, Indira; Ghimire, Binod; Joshi, Surendra Prasad (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This research examines policyholders’ satisfaction in life insurance companies, focusing on the influence of customer-centric strategies, particularly agency role, service quality, and organizational trustworthiness.Design/methodology/approach: The study employs descriptive and causal-comparative research approaches, with data collected from a sample of 390 life insurance policyholders residing in Kathmandu Valley.Findings: The findings revealed a significant relationship between agency role, organizational trustworthiness, service quality, and overall post-purchase experience, with organizational trustworthiness having the most significant impact.Conclusion: Preserving consumer trust and developing a favorable corporate image are essential for insurers, as trust and agent performance directly affect policyholders’ satisfaction.Implication: Focusing on trust-building activities, enhancing service quality, and understanding demographic differences can help insurers improve satisfaction, loyalty, and develop personalized marketing and service strategies.Originality/value: The study highlights context-specific insights into how customer-centric strategies affect life insurance satisfaction in an emerging market and recommends further research into specific aspects of agency role, trust, and service quality to achieve targeted improvements.JEL Classification: G22, M31, D12, L84